Vaccine-Induced Protection Against Furunculosis Involves Pre-emptive Priming of Humoral Immunity in Arctic Charr - Braden, Laura M.; Whyte, Shona K.; Brown, Alyson B. J.; Iderstine, Carter Van; Letendre, Corinne; Groman, David; Lewis, Jeff; Purcell, Sara L.; Hori, Tiago; Fast, Mark D. (Frontiers in Immunology, 2019)
With respect to salmonid aquaculture, one of the most important bacterial pathogens due to high mortality and antibiotic usage is the causative agent of typical furunculosis, Aeromonas salmonicida spp. salmonicida (Asal). In Atlantic salmon, Salmo salar, the host response during infections with Asal is well documented, with furunculosis outbreaks resulting in significant mortality in commercial settings. However, less is known about the host-pathogen interactions in the emerging aquaculture species, Arctic charr Salvelinus alpinus. Furthermore, there is no data on the efficacy or response of this species after vaccination with commonly administered vaccines against furunculosis. To this end, we examined the immunological response of S. alpinus during infection with Asal, with or without administration of vaccines (Forte Micro®, Forte Micro® + Renogen®, Elanco Animal Health). Artic charr (vaccinated or unvaccinated) were i.p.-injected with a virulent strain of Asal (106 CFUs/mL) and tissues were collected pre-infection/post-vaccination, 8, and 29 days post-infection. Unvaccinated Arctic charr were susceptible to Asal with 72% mortalities observed after 31 days. However, there was 72-82% protection in fish vaccinated with either the single or dual-vaccine, respectively. Protection in vaccinated fish was concordant with significantly higher serum IgM concentrations, and following RNA sequencing and transcriptome assembly, differential expression analysis revealed several patterns and pathways associated with the improved survival of vaccinated fish. Most striking was the dramatically higher basal expression of complement/coagulation factors, acute phase-proteins, and iron hemostasis proteins in pre-challenged, vaccinated fish. Remarkably, following Asal infection, this response was abrogated and instead the transcriptome was characterized by a lack of immune-stimulation compared to that of unvaccinated fish. Furthermore, where pathways of actin assembly and FcR-mediated phagocytosis were significantly differentially regulated in unvaccinated fish, vaccinated fish showed either the opposite regulation (ForteMicro®), or no impact at all (ForteMicro®+Renogen®). The present data indicates that vaccine-induced protection against Asal relies on the pre-activation and immediate control of humoral immune parameters that is coincident with reduced activation of apoptotic (e.g., NF-kappa B) and actin-associated pathways.